The role of pharmaceutical industry in building resilient health system - Saxena, Kanika; Balani, Sunita; Srivastava, Pallavi (Frontiers in Public Health, 2022)
Objectives This study explores the interrelationship among the current sustainability agenda of the pharmaceutical industry, based on the United Nation sustainable development goals (SDGs), the elements of the Joint External Evaluation (JEE) tool, and the triad components of the One Health approach. Methods A cross-walk exercise was conducted to identify commonalities among SDGs, JEE assessment tool, and One Health approach. An in-depth study of 10 global pharmaceutical firms' corporate sustainability reports and COVID-19 response plan for 2019–2020 was also conducted. Results The result of the exercise showed the existence of a direct and indirect relationship among the SDGs, elements of JEE assessment tool, and One Health approach. For example, both no poverty (SDG 1) and zero hunger (SDG 2) are linked with food safety targets under the JEE and with human and animal health under the One Health approach. Conclusion This study adds a new dimension emphasizing the possibility of tailoring the pharmaceutical industry's activities under the sustainability agenda to strengthen global health security while remaining consistent with the One Health approach.